Transformation of Civics education through digital-interactive models: Strategies for strengthening students' civic responsibility - Rika Sartika; Intan Indah Megasari (Inovasi Kurikulum, 2025)
The development of digital technology has changed the paradigm of learning in higher education, including in Civic Education (PKn) courses. This transformation presents opportunities for pedagogical innovation and challenges in shaping students' civic character. This study aims to analyze the effectiveness of a digital-interactive PKn learning model in strengthening students' civic responsibility at the Indonesia University of Education and the Bandung Institute of Technology. Using an exploratory sequential mixed methods design, this study involved five qualitative informants (lecturers and students) and 53 quantitative respondents. The results show that the digital-interactive model increases participation in discussions, strengthens critical thinking skills, and fosters digital ethics and constitutional awareness. However, obstacles remain in lecturers' TPACK competence, infrastructure readiness, and students' perceptions of PKn as a general course. This study concludes that the digital-interactive model is effective in building civic responsibility when supported by lecturer training, adaptive curriculum, and equitable access to technology. Recommendations aim to strengthen institutional policies and develop open educational resources (OER) to realize transformative PKn learning in the digital era.   Abstrak Perkembangan teknologi digital telah mengubah paradigma pembelajaran di pendidikan tinggi, termasuk dalam mata kuliah Pendidikan Kewarganegaraan (PKn). Transformasi ini menghadirkan peluang inovasi pedagogis sekaligus tantangan dalam pembentukan karakter kewarganegaraan mahasiswa. Penelitian ini bertujuan untuk menganalisis efektivitas model pembelajaran PKn digital-interaktif dalam memperkuat civic responsibility mahasiswa di Universitas Pendidikan Indonesia dan Institut Teknologi Bandung. Menggunakan desain exploratory sequential mixed methods, penelitian ini melibatkan lima informan kualitatif (dosen dan mahasiswa) serta 53 responden kuantitatif. Hasil menunjukkan bahwa model digital-interaktif meningkatkan partisipasi diskusi, memperkuat kemampuan berpikir kritis, dan menumbuhkan etika digital serta kesadaran konstitusional. Namun, kendala masih ditemukan pada kompetensi TPACK dosen, kesiapan infrastruktur, dan persepsi mahasiswa terhadap PKn sebagai mata kuliah umum. Penelitian ini menyimpulkan bahwa model digital-interaktif efektif membangun tanggung jawab kewarganegaraan bila didukung pelatihan dosen, kurikulum adaptif, dan akses teknologi yang merata. Rekomendasi diarahkan pada penguatan kebijakan institusional dan pengembangan open educational resources (OER) untuk mewujudkan pembelajaran PKn yang transformatif di era digital. Kata Kunci: pendidikan kewarganegaraan; sumber belajar terbuka; tanggung jawab kewargaan; Technological Pedagogical Content Knowledge; TPACK